Water-absorbent resin composition and method for producing water-absorbent resin
The water-absorbing resin composition with hydrolyzed collagen addresses biodegradability and performance issues, offering high absorbency and drying properties for sanitary and industrial uses.
Patent Information
- Application Number
- JP2023151921
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-12
- Filing Date
- 2023-09-20
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-09-20
AI Technical Summary
Conventional water-absorbing resins face issues with poor biodegradability, complicated disposal processes, and performance degradation after liquid absorption, failing to meet the requirements of modern sanitary products.
A water-absorbing resin composition containing hydrolyzed collagen, a carboxylic acid group-containing monomer solution, a crosslinking agent, and a polymerization initiator, with specific neutralization and polymerization processes to achieve high water absorption, drying properties, and appropriate biodegradability.
The resin composition exhibits high water absorbency, low liquid reversion, and controlled biodegradability, suitable for personal hygiene products and various industrial applications.
Smart Images

Figure 2025013088000001 
Figure 2025013088000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a water-absorbent resin composition, and more particularly to a water-absorbent resin composition which contains hydrolyzed collagen and has high water absorbency, high drying property and suitable biodegradability. [Background technology]
[0002] The water-absorbing resin is a polymeric material capable of absorbing and retaining liquid, and the mass of the liquid that can be absorbed can be 50 to 500 times or more the weight of the water-absorbing resin itself. Since the water-absorbing resin has excellent water absorption properties, in addition to personal hygiene products (e.g., baby diapers, feminine hygiene products, disposable wipes and / or adult diapers), it can also be applied to the agricultural and horticultural industries (e.g., water retention agents), the construction industry (e.g., condensation prevention agents), the petroleum industry (e.g., dehydration agents), the cable manufacturing industry (e.g., waterproof coating agents), the pharmaceutical industry (e.g., wound dressings) and the leisure industry (e.g., inflatable toys, artificial snow), etc.
[0003] The wide application of the water absorbent resin also poses a problem of waste. Conventional disposal methods include incineration or soil burial, but incineration causes further pollution problems such as air pollution and carbon emissions, and soil burial is limited by the low decomposition efficiency of the water absorbent resin by organisms, and still places a heavy burden on the environment.
[0004] Therefore, biodegradable water-absorbent resins are a new research direction. Japanese Patent Publication No. 1999-343339 discloses a water-absorbent resin produced by the co-reaction of poly-γ-glutamic acid and polyepoxide. US Patent Publication No. 20170002098 discloses the use of polysaccharide hydrogel. Mainland China Patent Publication Nos. 1410463 and 1846544 disclose the use of biological materials such as konjac flour and yacon as crosslinking agents, respectively. Republic of China Invention Patent I432501B discloses the addition of an unsaturated double bond compound or an epoxy resin compound to carry out a polymerization reaction.
[0005] The above methods are useful for the disposal of waste water-absorbing resins, but the polysaccharide compounds have the disadvantage of complicated processing processes, and the obtained water-absorbing resins have problems such as being too soft after absorbing water and lowering in performance, and cannot achieve the functions required for current sanitary products. Poly-γ-glutamic acid needs to be produced by a microbial culture method, and therefore needs to be sterilized before use, which not only increases the production cost but also makes the production process more complicated. Water-absorbing resins using starch as a copolymer have high biodegradability, but starch is prone to yellowing in the heat treatment process, which gives consumers an uncomfortable feeling. The biodegradability of water-absorbing resins can be improved by adding unsaturated double bond compounds or epoxy resin compounds to carry out a polymerization reaction, but if natural materials can be used, the dependency on petrochemical raw materials can be further reduced. Summary of the Invention [Problem to be solved by the invention]
[0006] Therefore, in order to solve the above problems, there is an urgent need for a water-absorbing resin having high water absorbency, high drying property and suitable biodegradability. [Means for solving the problem]
[0007] Accordingly, one aspect of the present invention provides a water-absorbent resin composition comprising hydrolyzed collagen.
[0008] Another aspect of the present invention provides a method for producing a water-absorbent resin, in which the resulting water-absorbent resin has high water absorbency, high drying property and suitable biodegradability by adding hydrolyzed collagen.
[0009] According to the above aspect of the present invention, there is proposed a water absorbent resin composition comprising: an aqueous solution of a carboxylic acid group-containing monomer having a neutralization rate of 45 mol% or more and a pH value of 7.0 or less; hydrolyzed collagen; a crosslinking agent; and a polymerization initiator including a thermal decomposition initiator and / or a redox initiator.
[0010] In one embodiment of the present invention, the molecular weight of the hydrolyzed collagen is ≧1 KDa and less than 10 KDa.
[0011] In one embodiment of the present invention, the amount of hydrolyzed collagen used is 0.1% by weight to 20% by weight based on 100% by weight of the water-absorbent resin composition.
[0012] In one embodiment of the present invention, the water-absorbing resin composition may optionally include a surface treatment agent.
[0013] In one embodiment of the present invention, the hydrolyzed collagen is obtained by hydrolyzing fish scales with proteolytic enzymes.
[0014] In one embodiment of the invention, the proteolytic enzyme is a serine endoprotease.
[0015] According to another aspect of the present invention, a method for producing a water-absorbent resin is proposed, which includes the following steps: A neutralization step is performed on an aqueous solution of a carboxylic acid monomer with a basic compound to obtain an aqueous solution of a carboxylic acid group-containing monomer having a neutralization rate of 45 mol % or more and a pH value of 7.0 or less.
[0016] Next, the carboxylic acid group-containing monomer aqueous solution, the hydrolyzed collagen obtained by hydrolyzing the fish scales with a protease, the crosslinking agent, and the polymerization initiator are mixed together to carry out a radical polymerization reaction, thereby obtaining a water-absorbent resin. Finally, after the radical polymerization reaction, a drying process is carried out to obtain a water-absorbent resin.
[0017] In one embodiment of the present invention, the method for preparing the water-absorbing resin may optionally include subjecting the water-absorbing resin to a surface cross-linking treatment.
[0018] In one embodiment of the invention, the proteolytic enzyme is a serine endoprotease.
[0019] In one embodiment of the present invention, the molecular weight of the hydrolyzed collagen is ≧1 KDa and less than 10 KDa.
[0020] By applying the water-absorbent resin composition containing hydrolyzed collagen and the method for producing a water-absorbent resin of the present invention, the obtained water-absorbent resin can have high water absorbency, high drying properties, and appropriate biodegradability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] As described above, the present invention provides a water-absorbent resin composition containing hydrolyzed collagen, which can obtain a water-absorbent resin having high water absorbency, high drying property and suitable biodegradability, and can further obtain an absorbent body after being mixed with a fiber substrate.
[0022] The term "water absorption" as used herein refers to the ability of the water-absorbing resin to absorb liquid. The liquid may be pure water or an aqueous solution. In some embodiments, the aqueous solution may include, but is not limited to, saline solution, urine, menstrual blood, soil water, or aqueous solutions in other application environments. It should be noted that the weight of the salt-containing aqueous solution that can be absorbed by the water-absorbing resin is smaller than that of pure water, since the salts affect the water-absorbing ability of the water-absorbing resin. To simulate the actual usage situation, the water-absorbing ability of the water-absorbing resin may be evaluated using saline solution or synthetic urine.
[0023] In some embodiments, the water absorbency may be evaluated using the absorption capacity (also called free swell capacity, FSC), which is the ratio of the weight of the liquid absorbed by the water absorbent polymer to the dry weight of the liquid not absorbed by the water absorbent polymer when no external force is applied to the water absorbent polymer.
[0024] In another embodiment, the water absorbency may be evaluated when the water absorbent resin is subjected to an external force. In some embodiments, the water absorbency may be evaluated using a centrifuge retention capacity (CRC), which is the ratio of the weight of the liquid remaining in the water absorbent resin after the water absorbent resin absorbs the liquid and centrifuges it to the dry weight of the liquid not absorbed by the water absorbent resin.
[0025] In some embodiments, absorbency may be evaluated using absorption against pressure (AAP), which is the ratio of the weight of liquid absorbed by the absorbent polymer to the dry weight of liquid not absorbed by the absorbent polymer after the absorbent polymer has absorbed the liquid for a certain period of time when subjected to a certain pressure.
[0026] In some embodiments, the water absorption may be evaluated using the absorption index against pressure (AAP), which is the ratio of the core shell absorption against pressure (CS AAP) to the water absorption against pressure. The core shell absorption against pressure is similar to the evaluation method of the absorption index against pressure, but differs in that the water absorption time of the core shell absorption against pressure is long.
[0027] The term "high water absorbency" as used herein means that the absorbency of the water absorbent resin is 50 g / g or more, the absorbency against pressure is 15 g / g or more, preferably 20 g / g or more, more preferably 30 g / g or more, and the absorbency index against pressure is 0.8 or more. Experiments have demonstrated that the absorbency of the water absorbent resin of the present invention is 50 g / g to 65 g / g, the absorbency against pressure is 20 g / g to 30 g / g, and the absorbency index against pressure is 0.8 or more and less than 0.9.
[0028] The term "dryness" as used herein means the degree of difficulty with which the absorbent resin releases liquid after absorbing the liquid. In some embodiments, the dryness may be evaluated using the return amount of an absorbent body made of the absorbent resin, the return amount being the weight of liquid released after the absorbent body absorbs liquid and is subjected to pressure. The term "high dryness" as used herein means that the return amount is less than 5 g. Experiments have demonstrated that the return amount of an absorbent body made of the absorbent resin of the present invention is less than 5 g, for example, 0.1 g to 2.0 g, or 0.5 g to 1.5 g.
[0029] The term "biodegradability" as used herein means the degree of difficulty with which microorganisms can degrade the water-absorbent resin. In some embodiments, the biodegradability may be evaluated using the gel strength of the water-absorbent resin after treatment with L-ascorbic acid. It should be noted that L-ascorbic acid or its salts can swell and degrade the water-absorbent resin, contributing to the biodegradation of the water-absorbent resin. However, L-ascorbic acid and its salts are also present in liquids such as urine, menstrual blood, and soil water, and if the gel strength of the water-absorbent resin after treatment with L-ascorbic acid is too low, the durability of the absorbent body produced is low, so it is necessary to control the biodegradability within an appropriate range.
[0030] "Suitable biodegradability" as described herein means that the gel strength of the water absorbent resin is 100g-200g after 3 hours of treatment with L-ascorbic acid, and 50g-110g after 24 hours of treatment with L-ascorbic acid. Experiments have demonstrated that the water absorbent resin of the present invention has a gel strength of 100g-150g, or 110g-135g after 3 hours of treatment with L-ascorbic acid, and a gel strength of 50g-80g, or 50g-75g after 24 hours of treatment with L-ascorbic acid.
[0031] In order to provide the water-absorbent resin with high water absorption, high drying property and suitable biodegradability, hydrolyzed collagen is added in the present invention. More specifically, the water-absorbent resin composition contains an aqueous solution of a carboxylic acid group-containing monomer, hydrolyzed collagen, a crosslinking agent and a polymerization initiator.
[0032] The carboxylic acid group-containing monomer aqueous solution can be obtained by dissolving a carboxylic acid-based monomer compound in water, followed by a neutralization step with a basic compound. The carboxylic acid-based monomer compound can include, but is not limited to, an acrylic acid compound, other suitable carboxylic acid group-containing monomer compounds, or any mixture of the above compounds. In some embodiments, the acrylic acid compound can include, but is not limited to, acrylic acid, methacrylic acid, ethyl acrylic acid-2-carboxylate, ethyl methacrylic acid-2-carboxylate, methyl acrylate, and / or ethyl acrylate. In some embodiments, the carboxylic acid group-containing monomer compound can optionally include other water-soluble monomers having acid groups and unsaturated double bonds, which can include, but are not limited to, 2-acrylamido-2-methylpropanesulfonic acid, maleic acid, fumaric acid, and / or other suitable water-soluble monomers. In other embodiments, other hydrophilic monomers having unsaturated double bonds can be selectively added to the carboxylic acid group-containing monomer aqueous solution. Other hydrophilic monomers having unsaturated double bonds may be, for example, maleic anhydride, fumaric anhydride, acrylamide, methacrylamide, dimethylaminopropylacrylamide, acrylamidopropyltrimethylammonium chloride.
[0033] The concentration of the carboxylic acid monomer aqueous solution may be, for example, 20% by weight to 55% by weight, or 30% by weight to 45% by weight. The concentration of the carboxylic acid monomer aqueous solution is easy to adjust within this range, and the reaction heat of the subsequent radical reaction is easy to control. The produced water absorbent resin can have preferable mechanical properties and is advantageous for machining.
[0034] The neutralization step of the aqueous carboxylic acid monomer solution may be performed by a basic compound. In some embodiments, the basic compound may include, but is not limited to, an alkali metal compound, an alkaline earth compound, other suitable basic compounds, or any mixture of the above compounds. In some embodiments, the basic compound may include, but is not limited to, a basic compound having a hydroxyl group, a compound having a carbonate group, other suitable basic compounds, or any mixture of the above materials. In some embodiments, the basic compound may include, but is not limited to, sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, and / or ammonia compounds.
[0035] When carrying out the neutralization step, the basic compound is gradually added to the aqueous carboxylic acid monomer solution, and the drop ratio of the basic compound to the aqueous carboxylic acid monomer, in terms of volume, may be, for example, 0.80 or more and less than 1.00, or 0.85 to 0.95. The neutralization step may be carried out for 1 hour to 3 hours to control the temperature of the aqueous carboxylic acid monomer solution to 15°C to 40°C.
[0036] After the neutralization step, some of the carboxylic acids in the obtained aqueous solution of the carboxylic acid group-containing monomer form sodium salts, potassium salts or ammonium salts, which affect the dissociation of the hydrophilic groups, and thus improve the water absorption of the produced water absorbent resin. However, if the content of the carboxylic acid group in the aqueous solution of the carboxylic acid group-containing monomer is too low, the structure of the produced water absorbent resin may be destroyed, and the water absorption of the resin may be reduced. Therefore, in the neutralization step, it is necessary to control the content of the carboxylic acid group in the aqueous solution of the carboxylic acid group-containing monomer.
[0037] The carboxylic acid group content in the aqueous solution of a carboxylic acid group-containing monomer may be evaluated by the neutralization ratio. The neutralization ratio refers to the content of neutralized carboxylic acid groups in the aqueous solution of a carboxylic acid group-containing monomer. Based on 100 mol% of the carboxylic acid content in the aqueous solution of a carboxylic acid group-containing monomer that has not been subjected to a neutralization step, the neutralization ratio of the aqueous solution of a carboxylic acid group-containing monomer may be 45 mol% or more, for example, 45 mol% to 85 mol%, or 50 mol% to 75 mol%.
[0038] The carboxylic acid group content in the aqueous solution of the carboxylic acid group-containing monomer may be evaluated by pH value, and the pH value of the aqueous solution of the carboxylic acid group-containing monomer is 7.0 or less, for example, 5.0 to 7.0, or 5.5 to 6.5. If the pH value of the aqueous solution of the carboxylic acid group-containing monomer is greater than 7.0, the produced water absorbent resin not only has a defect such as a large content of residual monomers and a reduced water absorbency, but also has a problem of being prone to cause skin allergies when in contact with the skin. If the pH value of the aqueous solution of the carboxylic acid group-containing monomer is 5.0 to 7.0, the produced water absorbent resin has a small content of residual monomers and is excellent in water absorbency.
[0039] The aqueous solution of the carboxylic acid group-containing monomer may optionally contain a water-soluble polymer. The molecular weight of the water-soluble polymer is not particularly limited, but it is understood that the molecular weight of the water-soluble polymer added does not affect the water absorption of the produced water-absorbing resin. In some embodiments, the water-soluble polymer may include, but is not limited to, partially or completely saponified polyvinyl alcohol, polyethylene glycol, polyacrylic acid, polyacrylamide, starch and / or starch derivatives (e.g., methyl cellulose, methyl cellulose acrylate and / or ethyl cellulose). In some embodiments, the water-soluble polymer may be starch and / or partially or completely saponified polyvinyl alcohol.
[0040] In order to make the produced water absorbent resin have excellent water absorbency, the amount of the water soluble polymer used may be 0% by weight to 20% by weight, for example, more than 0% by weight to 10% by weight, or more than 0% by weight to 5% by weight, based on 100% by weight of the carboxylic acid group-containing aqueous monomer solution.
[0041] Hydrolyzed collagen is obtained after subjecting collagen to a hydrolysis process. The origin of collagen is not particularly limited and may be derived from the skin, bone or cartilage of terrestrial animals such as cows, pigs or poultry, or the skin, bones, fins, scales and / or swim bladder of aquatic animals. In some embodiments, collagen may be derived from milkfish scales.
[0042] The hydrolysis step may include, but is not limited to, acid hydrolysis, base hydrolysis, and / or enzymatic hydrolysis. For enzymatic hydrolysis, see the literature review "Biological activity of peptides purified from fish skin hydrolysates" by Racheal Abuine et al., published in Fisheries and Aquatic Sciences, Vol. 22, No. 10, 2019, and the article "Study on the antioxidant activity of enzymatic hydrolysis solution of hydrolyzed collagen of tilapia scales" by Lai Zhixing et al., published in Fisheries Research, p. 99-108, 2007, all of which are incorporated herein by reference, and the Republic of China Patent Publication No. TW 200831005A. In some embodiments, the hydrolyzed collagen may be a commercially available product, such as fish scale hydrolyzed collagen (product name FCMB101) produced by Nuowant Biomedical Technology Co., Ltd.
[0043] The type of protease is not particularly limited. In some embodiments, the protease may be an endoprotease, depending on whether the protease acts on the end of collagen. In some embodiments, the protease may include, but is not limited to, serine proteases, threonine proteases, cysteine proteases, aspartic proteases, glutamic acid proteases, and / or metalloproteases, depending on the amino acid classification of the activation site where the protease acts. In some embodiments, the protease may be alcalase, papain, and / or bromelain. It should be further explained that ALCALASE may be a protease of Bacillus licheniformis, which is one of the serine endopeptidases.
[0044] The amount of hydrolyzed collagen used may be 0.1% by weight to 20% by weight, for example, 0.5% by weight to 10% by weight, or 0.5% by weight to 5% by weight, based on 100% by weight of the aqueous carboxylic acid group-containing monomer solution. When the amount of hydrolyzed collagen used is within the above range, the produced water absorbent resin has high drying properties and appropriate biodegradability.
[0045] The molecular weight of the hydrolyzed collagen may be, for example, 1 KDa or more and less than 10 KDa, for example, 1 KDa or more and 5 KDa or less. When the molecular weight of the hydrolyzed collagen is in this range, the produced water-absorbent resin can have high water absorbency, high drying property, and suitable biodegradability.
[0046] After mixing the aqueous solution of the carboxylic acid group-containing monomer and the hydrolyzed collagen, add a crosslinking agent and a polymerization initiator to carry out a radical polymerization reaction. The radical polymerization reaction may be carried out in a batch reactor or a belt reactor. After the radical polymerization reaction, the hydrolyzed collagen can be physically dispersed into a crosslinked structure.
[0047] When performing a radical polymerization reaction, the water absorbent resin produced by the crosslinking agent can have an appropriate crosslinking degree and form a gel body, and the gel body can have appropriate processability. The type of crosslinking agent is not particularly limited and may include a compound having at least two unsaturated double bond groups, a compound having at least two epoxy groups, other suitable crosslinking agents, or any mixture of the above compounds. In some specific examples, the compound having at least two unsaturated double bond groups is N,N'-bis(2-propenyl)amine, N,N'-methylenebisacrylamide, N,N'-methylenebismethacrylamide, propenyl acrylate, ethylene glycol diacrylate, polyethylene glycol diacrylate, ethylene glycol dimethacrylate, polyethylene glycol dimethacrylate, glycerin triacrylate, glycerin trimethacrylate, ethylene oxide added triacrylate to glycerin ... In some embodiments, the compound having at least two unsaturated double bond groups may include, but is not limited to, sorbitol polyglycidyl ether, polyglycerol polyglycidyl ether, ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, and / or diglycerol polyglycidyl ether.
[0048] The amount of the crosslinking agent used may be, for example, 0.001 to 5 parts by weight, for example, 0.01 to 3 parts by weight, based on 100 parts by weight of the solid content of the water absorbent resin composition. When the amount of the crosslinking agent used is within the above range, the mechanical properties of the formed gel body are favorable, which is advantageous for machining.
[0049] The polymerization initiator can decompose to generate radicals, which can induce the radical polymerization reaction and further form a gel body. The polymerization initiator of the present invention can include, but is not limited to, a thermal decomposition type initiator, a redox type initiator, other suitable polymerization initiators, or any mixture of the above materials. In some embodiments, the redox type initiator can include acid sulfite, thiosulfate, ascorbic acid or ferrous salt, sodium hydrogen sulfate, and / or ammonium persulfate. In some embodiments, the thermal decomposition type initiator can include hydrogen peroxide (i.e., hydrogen peroxide solution), di-tert-butyl peroxide, peroxyamide, persulfate (e.g., ammonium salt or alkali metal salt, etc.), and / or azo compound (e.g., 2,2'-azobis(2-amidinopropane) dihydrochloride or 2,2'-azobis(N,N-dimethyleneisobutylamidine) dihydrochloride, etc.).
[0050] When the polymerization initiator contains both a thermal decomposition initiator and a redox initiator, the redox initiator can first decompose to generate radicals, and then induce the first stage radical polymerization reaction. At the same time, the reaction heat generated by the first stage radical polymerization reaction can decompose the thermal decomposition initiator, and induce the second stage radical polymerization reaction, and further improve the reactivity of the radical polymerization reaction.
[0051] Based on 100% by weight of the neutralized carboxylic acid group monomer compound, the amount of the polymerization initiator used is 0.001% by weight to 10% by weight, for example, 0.1% by weight to 5% by weight. When the amount of the polymerization initiator used is 0.001% by weight to 10% by weight, the radical polymerization reaction can have appropriate reactivity, and the produced water absorbent resin can be prevented from forming a solid rather than a gel due to an excessively high degree of polymerization.
[0052] After the radical polymerization reaction, a drying step is further performed to obtain a water absorbent resin. The drying step can effectively remove the moisture and residual monomers in the gel body. Therefore, the dried water absorbent resin has higher water absorption than a water absorbent resin that has not been subjected to a drying step. In some embodiments, in order to effectively remove the moisture and residual monomers in the water absorbent resin and control the degree of crosslinking of the water absorbent resin, the temperature of the drying step may be, for example, 100°C to 180°C, and the time of the drying step may be, for example, 1 hour to 3 hours.
[0053] Before carrying out the drying step, the gel body may be first subjected to a crushing step to obtain a gel mass. In some embodiments, the crushing step may be carried out by a cutter mill. The diameter of the gel mass may be, for example, 2.0 mm or less, or 0.03 mm to 1.5 mm. The gel mass having a diameter in the above range has favorable thermal conductivity and fine powder content, can contribute to the removal of residual monomers and moisture, and can avoid an increase in the manufacturing cost of subsequent processing. It should be noted that the narrower the particle size distribution of the gel mass, the higher the efficiency of the drying step and the higher the water absorption of the formed dried product.
[0054] After the drying step, the water absorbent resin can be further pulverized and sieved to obtain a water absorbent resin powder, and the diameter of the water absorbent resin powder may be, for example, 0.06 mm to 1.00 mm, or 0.10 mm to 0.85 mm, so as to achieve a high fine powder amount and water absorbency.
[0055] After the radical polymerization reaction and drying process, the water absorbent resin obtained has a uniform crosslinked structure, so that the water absorbent resin is an insoluble hydrophilic polymer. In order to further improve the water absorption properties of the water absorbent resin, such as the absorption speed, gel strength, blocking resistance, and liquid permeability, the surface of the water absorbent resin can be further crosslinked by selectively performing a surface crosslinking treatment on the water absorbent resin. The surface crosslinking treatment includes mixing a surface treatment agent with the water absorbent resin and heat treating it at 140°C to 160°C for 0.5 to 1.5 hours.
[0056] The surface treatment agent used in the surface cross-linking treatment may include, but is not limited to, a multifunctional cross-linking agent capable of reacting with a carboxylic acid group. In some embodiments, the surface treatment agent may include, but is not limited to, a polyol, a polyamine, a compound having at least two epoxy groups, an alkylene carbonate, other suitable cross-linking agents, or any combination of the above materials. In some embodiments, the surface treatment agent may include, but is not limited to, glycerin, ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, propylene glycol, 1,4-butanediol, ethylenediamine, diethylenediamine, triethylenediamine, sorbitol polyglycidyl ether, polyglycerol polyglycidyl ether, ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, diglycerol polyglycidyl ether, ethylene glycol carbonate, 4-methyl-1,3-dioxolan-2-one, 4,5-dimethyl-1,3-dioxolan-2-one, 4,4-dimethyl-1,3-dioxolan-2-one, 4-ethyl-1,3-dioxolan-2-one, 1,3-dioxan-2-one, 4,6-dimethyl-1,3-dioxan-2-one, and / or 1,3-dioxepan-2-one.
[0057] In order to achieve an appropriate crosslinking effect and improve the water absorption of the produced water absorbent resin, the amount of the surface treatment agent used may be, for example, 0.001 parts by weight to 10 parts by weight, and preferably 0.005 parts by weight to 5 parts by weight, based on 100 parts by weight of the water absorbent resin composition.
[0058] Depending on the form of the surface treatment agent, the surface treatment agent may be added directly to the water absorbent resin composition, or may be prepared as a crosslinking solution first and then added to the water absorbent resin composition. The crosslinking solution may be water or a hydrophilic organic solvent (e.g., methanol, ethanol, propanol, isobutanol, acetone, methyl ether, and / or ethyl ether). In some embodiments, the hydrophilic organic solvent may be preferably methanol or ethanol.
[0059] In some embodiments, the water-absorbing resin produced by the present invention can be applied to hygiene products such as diapers (e.g., low consistency pulp diapers (Fluffless, which uses a large amount of water-absorbing resin at the same time) or adult diapers), so that the diapers have high water absorbency, high dryness and suitable biodegradability.
[0060] In some applications, the water-absorbing resin can be used to manufacture an absorbent body. The absorbent body may be manufactured by mixing the water-absorbing resin with a fibrous substrate. Generally, the basis weight (weight per unit area) of the absorbent body is 0.01 g / cm 2 ~0.30g / cm 2 and the thickness of the absorbent body is 30 mm or less.
[0061] In some embodiments, the fibrous substrate may be a hydrophilic fiber, which contributes to liquid spreading and transport, and further improves the absorbency of the absorbent body. In some embodiments, the hydrophilic fiber may include, but is not limited to, ground wood pulp.
[0062] In some embodiments, the weight of the water-absorbent resin is 20% by weight or more and less than 100% by weight, for example, 40% by weight or more and less than 100% by weight, or 50% by weight or more and less than 100% by weight, based on the weight of the absorbent body (100% by weight).
[0063] In practical applications, the absorbent may be provided on the liquid-impermeable polyethylene film, and the absorbent may be provided with a liquid-permeable nonwoven fabric to form a composite laminate structure. According to the requirements of the application, in other applications, the composite laminate structure may not include a fiber substrate. In other words, the water-absorbing resin is directly provided on the polyethylene film, and the nonwoven fabric is provided on the water-absorbing resin. In these applications, the water-absorbing resin laid between the polyethylene film and the nonwoven fabric is not densely stacked, so that the water-absorbing resin has an expansion space and can absorb liquid more effectively.
[0064] The application of the present invention will be described below with reference to several examples, but these are not intended to limit the present invention, and a person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Preparation Example 1
[0065] 540g of acrylic acid and 583g of water were mixed to obtain an acrylic acid aqueous solution. Next, 437.5g of sodium hydroxide aqueous solution having a concentration of 48% by weight was dropped into the acrylic acid aqueous solution to carry out a neutralization process. The drop ratio of sodium hydroxide to acrylic acid was 0.85-0.95, the neutralization process time was 2 hours, and the temperature of the acrylic acid aqueous solution during the neutralization process was 15°C-40°C. After the neutralization reaction, an acrylic acid aqueous solution having a monomer concentration of 42% by weight was obtained, and 70 mol% of acrylic acid was neutralized to become sodium acrylate, and the pH of the acrylic acid aqueous solution was 5.71.
[0066] Next, an aqueous acrylic acid solution and 15.60 g of hydrolyzed collagen with a molecular weight of 1500 g / mol (product name: FCMB101, manufacturer: Noo Medical Technology Co., Ltd.) were added and mixed, after which 0.9 g of N,N'-methylenebisacrylamide was added and the temperature was maintained at about 20°C. Then, 3.6 g of sodium hydrogen sulfite, 3.6 g of ammonium persulfate, and 0.3 g of hydrogen peroxide were added to carry out a radical polymerization reaction to obtain a gel body. The gel body was pulverized with a cutter mill to obtain gel lumps with a particle size of 2.0 mm or less.
[0067] Next, the gel mass was dried at 130°C for 2 hours, and then sieved with a 0.10mm to 0.85mm sieve to obtain a powder. Then, 200g of the powder was added to 5g of a surface treatment agent and an organic solvent, and further heat-treated at 150°C for 1 hour, and cooled by standing to obtain a water-absorbent resin of Preparation Example 1. The surface treatment agent solution contained ethylene glycol and 1,4-butanediol (manufacturer: Taiwan Plastics Industry Co., Ltd.), the organic solvent contained methanol, and the volume ratio of ethylene glycol, 1,4-butanediol, and methanol was 1.0:1.0:0.5. Preparation Examples 2 to 5, Preparation Comparison Examples 1 to 3
[0068] The methods for producing water-absorbent resins in Preparation Examples 2 to 5 and Preparation Comparative Examples 1 to 3 are similar to Preparation Example 1, but differ in the amount of hydrolyzed collagen used, the molecular weight, and / or the preparation method. In detail, compared with the hydrolyzed collagen in Preparation Example 1, the amount of hydrolyzed collagen (product name: FCMB101, molecular weight 3000 g / mol) used in Preparation Example 2 was 15.60 g, the amount of hydrolyzed collagen (product name: FCMB101) used in Preparation Example 3 increased to 46.80 g, and the amount of hydrolyzed collagen (product name: FCMB101) used in Preparation Example 4 decreased to 7.80 g,
[0069] The hydrolyzed collagen added to the water absorbent resin of Preparation Example 5 was obtained by hydrolyzing collagen from fish scales with commercially available alcalase, and the amount used was 15.6 g. The hydrolysis process is briefly described below with reference to the article "Research on the antioxidant activity of the enzyme hydrolyzate of hydrolyzed collagen from tilapia scales" published by Yoshiyuki Yori et al. in Fisheries Research, pages 99 to 108, 2007. After acid decalcification treatment of the fish scales, proteolytic enzymes were added and hydrolysis was performed at 45°C to 55°C for 1 to 5 hours to obtain hydrolyzed collagen.
[0070] No hydrolyzed collagen was added to the water absorbent resin of Comparative Preparation Example 1, the amount of hydrolyzed collagen (product name: FCMB101) added to the water absorbent resin of Comparative Preparation Example 2 was reduced to 0.83 g, and the hydrolyzed collagen of the water absorbent resin of Comparative Preparation Example 3 was produced by the method described in Preparation Example 5, but its molecular weight is 10,000 g / mol (i.e., 10 KDa).
[0071] The detection of the molecular weight of the hydrolyzed collagen may be performed by liquid chromatography analysis, using a Superdex 30 increase column as the column, and the eluent contains 0.1 M sodium sulfate (Na2SO4), 0.02 M sodium dihydrogen phosphate (NaH2PO4) at pH 5.3, and 0.5% sodium dodecyl sulfate (SDS), and the flow rate of the eluent is 0.5 mL / min.
[0072] The amounts and molecular weights of hydrolyzed collagen used in Preparation Examples 1 to 5 and Preparation Comparative Examples 1 to 3 are recorded in Table 1. Preparation Example 6
[0073] 10.0 g of the water-absorbent resin produced in Preparation Example 1 and 10.0 g of crushed wood pulp were mixed in an absorbent body forming machine to obtain a mixture. Next, the mixture was molded using a wire mesh with a 400 mesh (i.e., a pore size of 38 μm) to obtain an absorbent body with an area of 160 cm2. 2 (8cm x 20cm). After that, the molded absorbent was placed on a polyethylene (PE) film and then covered with a nonwoven fabric. Next, a pressure of 18.39kPa (area 160cm2, weight 30kg) was applied to the absorbent, and after 5 minutes, the absorbent, polyethylene film, and nonwoven fabric were further bonded with a white adhesive around the periphery to obtain a test absorbent of Preparation Example 6. Preparation Examples 7 to 10 and Comparative Preparation Examples 4 to 6
[0074] The test absorbents of Preparation Examples 7 to 10 and Comparative Preparation Examples 4 to 6 are manufactured in a manner similar to that of the test absorbent of Preparation Example 6, but differ in that Preparation Examples 7 to 10 and Comparative Preparation Examples 4 to 6 use the water-absorbent resins of Preparation Examples 2 to 5 and Comparative Preparation Examples 1 to 3, respectively. Evaluation method
[0075] The absorbency, centrifugal retention capacity, absorbency under pressure, core-shell absorbency under pressure, absorption index under pressure, residual monomer and gel strength of the water absorbent resins of Preparation Examples 1 to 7 and Preparation Comparative Examples 1 to 3 are evaluated by the following evaluation methods, and the results are recorded in Table 1.
[0076] Next, the reversion amount of the test absorbents produced in Preparation Examples 6 to 10 and Preparation Comparative Examples 4 to 6 is evaluated by the following evaluation method, and the results are recorded in Table 2. It should be noted that unless otherwise specified, the measurements by the following evaluation method are performed at a temperature of 23±2°C and the relative humidity of the air is 45±10%. Before carrying out the evaluation method, the water-absorbent resin should be mixed thoroughly. holding power
[0077] The measurement method was according to ERT 441.3(10) specified by the European Disposables and Nonwovens Association (EDANA). Water absorption rate under pressure
[0078] The water absorbency against pressure of the water absorbent resin was evaluated according to the measurement method of ERT 442.3(10) specified by the European Nonwovens Council, and will be briefly described as follows. The initial weight of the water absorbent resin was measured, and then a pressure of 4.9 kPa was applied to the water absorbent resin to make the water absorbent resin absorb a sodium chloride aqueous solution with a concentration of 0.9% by weight for 60 minutes, after which the weight of the water absorbent resin after absorbing water was measured. The weight after absorbing water was divided by the initial weight to obtain the water absorbency against pressure. Core-shell water absorption capacity under pressure
[0079] The method for evaluating the core-shell water absorption capacity against pressure is similar to the evaluation method for the test method for water absorption capacity against pressure described above, but the time (240 minutes) for allowing the water absorbent resin to absorb the sodium chloride aqueous solution is long. Absorption index under pressure
[0080] The absorbency index under pressure was obtained by calculating the ratio of the core-shell water absorption capacity under pressure to the water absorption capacity under pressure. Residual Monomer
[0081] Residual monomers in the water-absorbent resin were evaluated according to the measurement method of ERT 410.3(10) specified by the European Nonwoven Fabrics Association. Absorption rate
[0082] The absorbency of the water-absorbent resin was evaluated according to the measurement method of ERT 420.3(10) specified by the European Nonwoven Fabrics Association. Gel Strength
[0083] 1.000±0.001g of the water-absorbent resin was gradually added to 30mL of physiological saline solution, stirred with a magnetic stirrer for 1 minute, and allowed to stand for 3 or 24 hours, after which the gel strength of the water-absorbent resin was detected with a STEVENS gel strength tester. The physiological saline solution contained 0.005% by weight of L-ascorbic acid, and the STEVENS gel strength tester was set so that the drop speed of the hanging column tube was 1.0mm / sec and the drop distance was 25cm. Backflow amount
[0084] Thirty pieces of filter paper were prepared, each with a size of 8 cm × 20 cm, and the initial weight (W1) of the 30 pieces of filter paper was measured. Next, a 7.8 kg filter with an area of 160 cm was 2 A pressure of 4.8 kPa was uniformly applied to the test absorbent by the weight, and 180 mL of synthetic urine was dropped in three portions at the center of the test absorbent every 30 minutes, and the synthetic urine was the synthetic urine described in US Patent Publication No. 20040106745. Next, the weight above the test absorbent was removed, and the 30 pieces of filter paper were placed on the test absorbent, and the weight was immediately placed on the 30 pieces of filter paper, and the filter paper was allowed to absorb the backflow liquid for 5 minutes, and then the weight (W2) of the 30 pieces of filter paper after absorption was measured. The difference between the weight (W2) of the 30 pieces of filter paper after absorption and the initial weight (W1) was calculated, and the backflow amount of the test absorbent against the synthetic urine was obtained. Evaluation results
[0085] [Table 1]
[0086] [Table 2]
[0087] As shown in Table 1, the absorbency under pressure of the water-absorbent resins of Preparation Examples 1 to 5 was greater than 15 g / g, the absorbency under pressure was 0.8 or more, and the return amount of the produced test absorbent was 3 g or less, which demonstrated that the water-absorbent resin still had good absorbency after adding hydrolyzed collagen.
[0088] Next, as shown in Table 1, after treatment with L-ascorbic acid for 3 hours and 24 hours, the gel strength of the water absorbent resins of Preparation Examples 8 to 12 was certainly lower than that of Preparation Comparative Examples 1 to 3, and it was shown that the biodegradability of the produced water absorbent resin was high when hydrolyzed collagen of an appropriate amount (e.g., greater than 0.83 g) and an appropriate molecular weight (e.g., less than 1000 g / mol to 10000 g / mol) was added.
[0089] Furthermore, compared to Comparative Preparation Examples 4 to 6, the amount of return of the test absorbents in Preparation Examples 8 to 12 was lower, indicating that absorbents made from absorbent resins containing added hydrolyzed collagen are less likely to release absorbed liquid even when subjected to external pressure, and have drying properties during use.
[0090] Next, as can be seen from the evaluation results of gel strength shown in Table 1, the water absorbent resin of the present invention significantly decreased in gel strength after immersion in L-ascorbic acid for 3 hours or 24 hours, and has good biodegradability.
[0091] As can be seen from the above examples, the water-absorbent resin composition and the method for producing the water-absorbent resin of the present invention have the following advantages: By adding hydrolyzed collagen, a water-absorbent resin having high water absorption, high drying property and suitable biodegradability can be produced, which can be widely applied to personal hygiene products such as baby diapers, feminine hygiene products, disposable wipes or adult diapers, or can be applied to the agricultural and horticultural industries, the construction industry, the petroleum industry, the cable manufacturing industry, the pharmaceutical industry and the leisure industry, etc.
[0092] Although the present invention has been disclosed above by a number of specific embodiments, it will be understood that various modifications, variations and substitutions may be made to the above disclosure, and that some features of the embodiments of the present invention may be adopted while other features are not correspondingly used without departing from the spirit and scope of the present invention. Therefore, the spirit and scope of the present invention should not be limited to those described in the above exemplary embodiments.
Claims
1. an aqueous solution of a carboxylic acid group-containing monomer having a neutralization rate of 45 mol % or more and a pH value of 7.0 or less; Hydrolyzed collagen, A cross-linking agent; A polymerization initiator including a thermal decomposition type initiator and / or a redox type initiator; A water-absorbing resin composition comprising:
2. 2. The water-absorbent resin composition according to claim 1, wherein the molecular weight of the hydrolyzed collagen is 1 KDa or more and less than 10 KDa.
3. 2. The water-absorbent resin composition according to claim 1, wherein the amount of the hydrolyzed collagen used is 0.1% by weight to 20% by weight based on 100% by weight of the water-absorbent resin composition.
4. The water-absorbing resin composition according to claim 1, further comprising a surface treatment agent.
5. 2. The water-absorbent resin composition according to claim 1, wherein the hydrolyzed collagen is obtained by hydrolyzing fish scales with a protease.
6. 2. The water-absorbent resin composition according to claim 1, wherein the protease is a serine endoprotease.
7. a step of neutralizing the aqueous carboxylic acid monomer solution with a basic compound to obtain an aqueous carboxylic acid group-containing monomer solution having a neutralization rate of 45 mol % or more and a pH value of 7.0 or less; a step of mixing the aqueous solution of the carboxylic acid group-containing monomer, the hydrolyzed collagen obtained by hydrolyzing fish scales with a protease, a crosslinking agent, and a polymerization initiator to carry out a radical polymerization reaction; A step of obtaining a water-absorbing resin by performing a drying step after the radical polymerization reaction; A method for producing a water-absorbing resin comprising the steps of:
8. The method for producing a water-absorbent resin according to claim 7, further comprising subjecting the water-absorbent resin to a surface cross-linking treatment.
9. The method for producing a water-absorbent resin according to claim 7, wherein the protease is a serine endoprotease.
10. The method for producing a water-absorbent resin according to claim 7, wherein the molecular weight of the hydrolyzed collagen is 1 KDa or more and less than 10 KDa.